1969
DOI: 10.1136/bmj.4.5677.206
|View full text |Cite
|
Sign up to set email alerts
|

Topical ampicillin in the appendicectomy wound: Report of double-blind trial

Abstract: Summary: One hundred and thirty unselected patients undergoing appendicectomy were treated with topical ampicillin powder or topical placebo powder (lactose) before closing the wound. The postoperative wound infection rates were 3% in the ampicillin-treated group and 24% in the control group, a significant difference.This difference was not influenced by the degree of inflammation in the appendix. No side-effects of treatment were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0
1

Year Published

1971
1971
1994
1994

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(25 citation statements)
references
References 15 publications
2
21
0
1
Order By: Relevance
“…Many workers have shown that a reduction in the incidence of wound infection can be attained by the use of topical ampicillin powder (Rickett and Jackson, 1969), povidone iodine spray (Gilmore et al, 1973), or irrigation of the wound with tetracycline D. A. Leigh, Kate Simmons, and Edelgard Norman solution (Longland, Gray, Lees, and Garrett, 1971;Benson, Brown, and Whittaker, 1973). The use of parenteral chemotherapy with penicillin, streptomycin, ampicillin, or tetracycline has not been shown to be successful in preventing wound infection (Magarey et a!, 1971;Longland et al, 1971), but three of these antibiotics have a very limited activity against bacteroides and the incidence of tetracycline resistance is relatively high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many workers have shown that a reduction in the incidence of wound infection can be attained by the use of topical ampicillin powder (Rickett and Jackson, 1969), povidone iodine spray (Gilmore et al, 1973), or irrigation of the wound with tetracycline D. A. Leigh, Kate Simmons, and Edelgard Norman solution (Longland, Gray, Lees, and Garrett, 1971;Benson, Brown, and Whittaker, 1973). The use of parenteral chemotherapy with penicillin, streptomycin, ampicillin, or tetracycline has not been shown to be successful in preventing wound infection (Magarey et a!, 1971;Longland et al, 1971), but three of these antibiotics have a very limited activity against bacteroides and the incidence of tetracycline resistance is relatively high.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative wound infection has been reported in up to 30% of cases (Lancet, 1971) and this incidence can be influenced by many factors, the most important being surgical skill and technique and the criteria used to define the infection. Bacteria play an important role in appendicitis and the local application of antibiotics (Forbes, 1961;Rickett and Jackson, 1969) or antiseptics (Gilmore, Martin,and Fletcher, 1973) can reduce the incidence of wound infection. Despite the large number of studies into the infective complications of appendicitis, few workers have produced a detailed description of the associated bacteriology, and anaerobic bacteria which account for over 90 % of the bacterial population of the intestine have rarely been reported.…”
mentioning
confidence: 99%
“…[5][6][7]11,12,16 Specifically, topical ampicillin was shown to reduce wound infection after colonic, 19 biliary and gastrointestinal surgery 20 and after appendectomy. 21,22 Ampicillin effectiveness is based on its activity against streptococci, enterococci and 30% of the E. coli isolates in our study. Its effectiveness against some aerobic and anaerobic bacteria has been also shown by hers.…”
Section: Discussionmentioning
confidence: 99%
“…The topical application of ampicillin powder to appendicectomy wounds has been shown to reduce the incidence of postoperative wound infection (Rickett and Jackson, 1969;Mountain and Seal, 1970). However, its value is not as yet widely accepted and further controlled trials have been suggested (Leading article, 1971).…”
mentioning
confidence: 99%